2019
DOI: 10.1136/fmch-2018-000043
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative study to identify the perception and challenges faced by the faculty of community medicine in the implementation of competency-based medical education for postgraduate students

Abstract: ObjectivesTo identify perception about the key aspects of competency-based medical education (CBME) among community medicine faculty members and to ascertain the various challenges faced by them during its implementation.MethodsA descriptive qualitative study of 2 months’ duration was conducted among the faculty members of the community medicine department. Non-probability purposive sampling was employed in the study. Free listing was done initially to elicit the views of faculty members to meet the intended o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 25 publications
0
6
0
1
Order By: Relevance
“…So far, CBME has been experimented in India only in few medical colleges for postgraduate education with good results but the outcome for undergraduates is awaited. 7 Systematic planning needs to be done, and the approach to medical education needs to be a given a new direction. 8 As faculty members are the forebearers to this new change, our study is an attempt to analyze the perceptions of the faculty and the likely challenges to be faced about the new curriculum.…”
Section: Ratio Of Faculty and Students Is Very Lessmentioning
confidence: 99%
“…So far, CBME has been experimented in India only in few medical colleges for postgraduate education with good results but the outcome for undergraduates is awaited. 7 Systematic planning needs to be done, and the approach to medical education needs to be a given a new direction. 8 As faculty members are the forebearers to this new change, our study is an attempt to analyze the perceptions of the faculty and the likely challenges to be faced about the new curriculum.…”
Section: Ratio Of Faculty and Students Is Very Lessmentioning
confidence: 99%
“…20 All these challenges can be tackled by proper capacity building and this will require a need-driven conduct of faculty development workshops to prepare the teachers for their roles. 20 The findings of a study done in Florida revealed that the workshops that were organized in the institution were not need driven. 21 The same suggestion we also found in our study and it clearly indicates that all the workshops should precede with needs assessment to enhance better acceptance and active engagement of the faculty members.…”
Section: Discussionmentioning
confidence: 99%
“…Similar sort of challenges was identified in a qualitative study done in South India, wherein it was recommended that the first step for the successful implementation of any initiative has to be faculty development. 20 All these challenges can be tackled by proper capacity building and this will require a need-driven conduct of faculty development workshops to prepare the teachers for their roles. 20 The findings of a study done in Florida revealed that the workshops that were organized in the institution were not need driven.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although CBME has been implemented worldwide and is a popular educational model for medical education, the literature describes several challenges related to CBME in postgraduate education ( 8 , 14 , 16 22 ). The challenges mentioned in literature can be categorized in three main themes, which are elaborated below: the practicality of CBME ( 20 22 ), the assessment burden ( 8 , 23 ) and also the developments in the work field ( 18 , 24 26 ). The practicality of CBME covers the way the educational concept is used and implemented.…”
Section: Introductionmentioning
confidence: 99%